2013
DOI: 10.4103/0972-2327.120494
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk for dementia across populations: A study on the prevalence of dementia in tribal elderly population of Himalayan region in Northern India

Abstract: Introduction:Studies have suggested that dementia is differentially distributed across populations with a lower prevalence in developing regions than the developed ones. A comparison in the prevalence of dementia across populations may provide an insight into its risk factors. Keeping this in view, a study was planned to evaluate the prevalence of dementia in tribal elderly population.Materials and Methods:A cross-sectional comprehensive two-phase survey of all residents aged 60 years and older was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…The current study was aimed at investigating the influence of level of literacy on dementia in a sample stratified by geography (Migrant, Urban, Rural and Tribal areas of sub-Himalayan state of Himachal Pradesh, India). This study extends our previous works [5][6][7] in Himachal Pradesh by examining the influence of literacy, post-hoc, on dementia. The study was based on the hypothesis that level of literacy does not influence dementia.…”
Section: Introductionsupporting
confidence: 68%
“…The current study was aimed at investigating the influence of level of literacy on dementia in a sample stratified by geography (Migrant, Urban, Rural and Tribal areas of sub-Himalayan state of Himachal Pradesh, India). This study extends our previous works [5][6][7] in Himachal Pradesh by examining the influence of literacy, post-hoc, on dementia. The study was based on the hypothesis that level of literacy does not influence dementia.…”
Section: Introductionsupporting
confidence: 68%
“…Various risk factors have been identified in the causation of AD in India. However, to the best of the knowledge of the author, there are no studies which assesses relationship of loneliness with AD [20].…”
Section: Psychiatric Disorders and Lonelinessmentioning
confidence: 99%
“…Recently, there has been extensive research on psychosocial effects of stress on neuroendocrine and immune systems. Whether loneliness qualifies as stress may be debatable [2,20,28]. However there is ample data, which gives evidence of immune system getting involved in loneliness.…”
Section: Bereavementmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] The alarming rise in the prevalence of PD in India has been attributed to the demographic pattern, changing environment, as well as lifestyle, [5] but some studies conducted in India reported that prevalence of PD in Indian population is lower compared with the western population. [6][7][8][9] In Karnataka, the prevalence of PD is reported to be 7 per 100,000. [10] In the later studies, the prevalence of PD above 50 years of age was 134 per 100,000.…”
Section: Introductionmentioning
confidence: 99%